1997
DOI: 10.1088/0953-8984/9/5/015
|View full text |Cite
|
Sign up to set email alerts
|

A structural transformation and its effect on the physical properties of the V-substituted system

Abstract: Systematic substitution of V in the system , 0.2, 0.4, 0.6, 0.8 and 1) was carried out in order to determine the effect of V ions on the phase formation and on the physical properties of the BSCCO 2223 system. The most interesting observation was structural transformation of the system from tetragonal to orthorhombic after . A solid solubility limit for V was also found to exist. Resistivity and susceptibility studies have shown that high- superconductivity exists up to and that the semiconducting-to-metalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In the last decade, there were many investigations have been made on κ(T) of high-T c materials [26][27][28][29][30][31][32][33][34][35][36][37] and almost the same results were obtained. In general, for κ(T) investigation of high-T c materials three important approaches can be considered to the total κ(T) calculations: (i) phonon contribution; (ii) electron contribution; and (iii) both electron and phonon contributions.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In the last decade, there were many investigations have been made on κ(T) of high-T c materials [26][27][28][29][30][31][32][33][34][35][36][37] and almost the same results were obtained. In general, for κ(T) investigation of high-T c materials three important approaches can be considered to the total κ(T) calculations: (i) phonon contribution; (ii) electron contribution; and (iii) both electron and phonon contributions.…”
Section: Introductionmentioning
confidence: 71%
“…Thermal conductivity, κ(T), investigation also gives important information about the scattering mechanism of charge carriers, electron-phonon interaction and other physical properties such as carrier density and phonon mean free path [26][27][28][29][30][31]. In the last decade, there were many investigations have been made on κ(T) of high-T c materials [26][27][28][29][30][31][32][33][34][35][36][37] and almost the same results were obtained.…”
Section: Introductionmentioning
confidence: 94%
“…After a small minimum, a sharp rise with a maximum and then a sharp drop were obtained just below T c . Such a feature has been observed in most substituted and/or unsubstituted HT c systems (Chanda and Dey, 1994;Bougrine et al, 1998Bougrine et al, , 2000Aksan et al, 1999;Yakıncı, 1997). The origin of this small minimum near T c is not clear but may be attributed to superconducting fluctuation contribution (Castellazi et al, 1997;Peacor et al, 1991;Yu et al, 1992).…”
Section: 5mentioning
confidence: 81%
“…2a). Most of the plate type crystals were considered to be c-axis oriented (according to the XRD investigations) and material has low porosity compared with the undoped BSCCO system [36]. The microqualitative analysis showed that plate type crystals were compositionally in the Bi 1.97 Sr 1.98 Ca 1.17 Cu 1.61 Mo 0.44 O 8+y form (the error is less than 1%).…”
Section: Scanning Electron Microscopy (Sem) and Energy Dispersive X-rmentioning
confidence: 99%
“…As in the metals and alloys the κ(T) investigations gives important information about the scattering mechanism of charge carriers, electron-phonon interactions and some other physical properties such as carrier density and mean free path [30][31][32][33][34][35][36]. Many investigations have been made on κ(T) properties of HT c materials and similar results were obtained [30][31][32][33][34][35][36][37][38][39][40][41][42]. But the results obtained for κ(T) calculations showed an unusual behavior compared to the conventional metallic structures [31,[37][38][39][40][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%